Animacy and Affectedness in Germanic Languages - Fleischhauer Jens (Open Linguistics, 2018)
This paper deals with the influence of animacy on affectedness. German, like other Germanic languages, requires oblique marking of the inanimate undergoer argument of verbs of contact by impact (e.g. hit, kick, bite), whereas the animate undergoer argument takes non-oblique marking. Inanimacy does not necessarily result in oblique marking; undergoer arguments with inanimate referents are realized in a non-oblique construction if a change of state or location is explicitly predicated, as in resultative constructions. This suggests that the marking of inanimate undergoer arguments is conditioned by two factors: animacy and affectedness. The basic claim is that animate and inanimate entities are affected differently by hitting, kicking and similar activities. Inanimates can only be physically affected, whereas animates can be psychologically affected as well. Since verbs of contact by impact do not entail a change of state/location, they do not represent their undergoer arguments as being (necessarily) physically affected. Hence, the potential psychological effect of hitting, kicking and the like on animate beings gives rise for interpreting animate undergoer arguments of those verbs as being affected.